Editorial [ Migraine Guest Editor: Dimos D. Mitsikostas ] - Dimos D. Mitsikostas (CNS & Neurological Disorders - Drug Targets, 2007)
Although less frequent among men, migraine affects almost one third of reproductive women, transforming this disorder into a significant public health problem with enormous socioeconomic impact. The last decade however, has seen a great improvement within both the scientific and the clinical fields: the 1988 international classification of headache disorders followed by the release of sumatriptan into the market opened novel avenues. For the first time, clear diagnostic criteria were established, and for the first time a drug targeting migraine, became available. After sumatriptan several other agonists at 5- HT1B and 5-HT1D receptors have been developed constituting a new antimigraine drug class, the so-called triptans. Limitations in their use, mainly due to vascular contraindications keep the field, searching for new potential targets that modulate pain neurotransmission exclusively within the trigeminovascular system. The recently cloned serotonin receptor subtypes 5-HT1F and the 5-HT7 have been shown to exert little or no vasoactive properties, and therefore are considered potential targets for antimigraine drugs with an improved safety profile. Apart from serotonin, other trigeminal and brainstem neurotransmission systems have been investigated. CGRP literature is probably the largest, following by reports implicating the glutamate receptors. CGRP receptor antagonists showed efficacy not only in animal models of migraine but in clinical trials as well. Adenosine and NO pathways are more recent targets. In addition to brain neurotransmission, modulation of cortical spreading phenomenon may influence migraine headache. Neuroimaging and genetic data shows promising results. Drugs with already proven prophylactic efficacy in migraine after well designed clinical trials analyses have also been found to modulate the cortical spreading depression in laboratory animals, suggesting that inhibition of cortical spreading depression phenomenon is an important pathway to control the migraine frequency and severity. Scientists working within the migraine field report in this issue the most recent achievements in their field. Undoubtedly, cephalic pain and migraine in particular, will be less resistant in the near future and patients suffering from these disorders will have the opportunity to get their lost quality of life back.